Sistem informasi manajemen: peran sistem informasi manajemen dalam era bisnis modren - Wirda neli; Rayyan Firdaus (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Management information systems (SIM) are a necessity needed by an organization or business to achieve effectiveness and work efficiency. Especially in the current era of modern business development. This article aims to analyze the role of management information systems in the modern business era.Information systems are a series of procedures, tools and technologies designed to collect, store, manage, and convey relevant information to management in an organization or business, sim forms the foundation for intelligent and effective decision-making. The basic concept of sim involves 3 components, namely infut, processing and output